PECULIARITIES OF SEMANTIC STRUCTURE OF NOUNS WITH MELIORATIVE EVALUATION IN THE SIGNIFICATIVE-DENOTATIVE COMPONENT OF DIRECT MEANING IN MODERN RUSSIAN - V. Gryaznova; A. Mamedova (Гуманитарные и юридические исследования)
The purpose of the article is to identify the features of the semantic structure of evaluative-characterizing nouns, in the signiicative-denotative component of the direct meaning of which there is a positive assessment. Based on the collected material, the authors identify two igurative meanings of such nouns: a) an evaluative-descriptive meaning (intermediate between direct and proper evaluative), b) an independent evaluative value, с) and the homonymous interjection that arose on their basis, as well as show the difference in the composition of markers that distinguish them. The authors attribute the evaluative-descriptive meaning, which is characterized by the coexistence of two main components: the positive evaluative as a vertex and the descriptive as an accompanying one, to semantic ambiguity as a kind of polysemicity, language or speech. Independent evaluative value, which has one main semantic component-pragmatic (emotional, emotional-aesthetic, emotional-ethical meliorative assessment), the authors refer to the classical polysemicity, which is the result of regular semantic development according to common language models of transfer (metaphorical, metonymic, associative). The limit of the development of the semantic structure of the studied evaluative-characterizing nouns is its destruction and the appearance of homonymous interjections that express emotion. In a signiicant number of texts of the modern Russian language the authors demonstrate mismatched markers highlighted their semantic phenomena: a) the use of the name in any grammatical form - use the name only in the form of the nominative case; b) the presence of lexical compatibility, enhancing the assessment, - the availability of lexical compatibility limiting and specifying the nature, с) the use of tokens in all possible for the name of the syntactic roles - the use of the token only in the predicate function, d) implementation of the evaluation function only - simultaneous presence of the nominative function - expression of emotion only. In general, the material studied allows the authors to conclude that the emotional lexicon of the modern Russian language is expanding and changing in accordance with the communicative needs of a native speaker